Comparison of Three Different Cord Clamping Techniques Regarding Oxidative–Antioxidative Capacity in Term Newborns - Kartal, İshak; Abbasoglu, Aslihan; Taysi, Seyithan (American Journal of Perinatology, 2022)
Objective As newborns are exposed to oxidative stress during delivery, cord clamping techniques play significant role on antioxidant status. In this study, we aimed to show the relationship between early cord clamping (ECC), delayed cord clamping (DCC), and cut–umbilical cord milking (C-UCM) techniques with total oxidant capacity (TOC), total antioxidant capacity (TAC), and peroxynitrite levels.Study Design Sixty-nine term infants were selected with Apgar's score of 7 and above in the 1 minute and 5 minutes. The mothers of all infants had uncomplicated pregnancy, had no congenital anomaly, and delivered by cesarean section. Newborns were randomized to one of three groups: ECC (n: 23), DCC (n: 23), or C-UCM (n: 23). After all newborn babies were taken under radiant heater, blood samples were collected from the UC. The plasma samples were then frozen and stored at −80°C until analysis and TOC, TAC, and peroxynitrite levels were studied.Results The ages of the mothers participating in the study were between 17 and 42 years, with an average of 29.14 ± 6.28. Thirty (43.5%) of the babies were girls and 39 (56.5%) were boys. The 5-minute Apgar's score of the babies in ECC group was significantly lower than the babies in DCC and cut cord milking group (p = 0.034; p = 0.034; p < 0.05). The TOC, oxidative stress index (OSI), and peroxynitrite measurements of three groups did not differ statistically. The TAC value of the C-UCM group was significantly higher than the patients with the ECC and DCC groups (p = 0.002; p = 0.019; p < 0.05).Conclusion C-UCM and DCC would be feasible methods by increasing antioxidant status and providing protective effect on the future health of the term newborns.Key Point
Keywords: umbilical cord; milking; oxidant; antioxidant; peroxynitritis